Enhancing communication, informed consent and recruitment in a paediatric urgent care surgical trial: a qualitative study - Frances C. Sherratt; Lucy Beasant; Esther M. Crawley; Nigel J. Hall; Bridget Young (BMC Pediatrics, 2020)
Abstract Background Recruiting patients to paediatric trials can be challenging, especially in trials that compare markedly different management pathways and are conducted in acute settings. We aimed to enhance informed consent and recruitment in the CONTRACT trial (CONservative TReatment of Appendicitis in Children a randomised controlled Trial; ISRCTN15830435) – a feasibility trial that compared non-operative treatment (antibiotics) versus appendicectomy for uncomplicated acute appendicitis. Methods Qualitative study embedded within CONTRACT and conducted across three UK children’s hospitals. Data were transcribed audio-recordings of 85 CONTRACT recruitment consultations with 58 families; and semi-structured interviews with 35 health professionals and 28 families (34 parents, 14 children) invited to participate in CONTRACT. Data analysis drew on thematic approaches. Throughout CONTRACT, we used findings from the ongoing qualitative analysis to inform bespoke communication training for health professionals recruiting to CONTRACT. Before and after training we also examined qualitative changes in communication during consultations and quantitative changes in recruitment rates. Results Bespoke communication training focussed on presenting the trial arms in a balanced way, emphasising clinical equipoise, exploring family treatment preferences and managing families’ expectations about the trial’s treatment pathways. Analysis of recruitment consultations indicated that health professionals’ presentation of treatment arms became increasingly balanced following training, (e.g. avoiding imbalanced terminology) and recruitment rose from 38 to 62%. However, they remained reluctant to explore families’ treatment preferences and respond with further information to balance these preferences. Analyses of interviews identified the time constraints of the urgent care setting, concerns about coercion, and reservations about exposing children to conversations about treatment risks as reasons for this reluctance. Interviews with families indicated the importance of clear explanations of trial treatment timings and sensitive communication of treatment allocation for both recruitment and retention. Conclusions Following bespoke training based on the qualitative analyses, health professionals presented CONTRACT to families in clearer and more balanced ways and this was associated with an increase in the recruitment rate. Despite training, health professionals remained reluctant to explore families’ treatment preferences. We provide several recommendations to enhance communication, informed consent, recruitment and retention in future trials in urgent care settings.